ROAD TRAFFIC VOLUME MALAYSIA 2023 (Highway Planning Division, Ministry of Works Malaysia, 2023)
This report is provided and useful for traffic consultants, planners, and developers in their individual applications and projects as it relates to the transportation, logistics, and development sectors in Malaysia